Using Teaching Resources to Help Students Develop Team and Project Skills Pays Off, Both in Terms of Employability and Shorter Study Time - Lars, Peter Jensen (2005)
Since Aalborg University in Denmark was started in 1974 it has been using a special educational model, where Problem Based Learning is the turning point. Each semester the students on the Engineering Educations form groups of approximately 6 persons, which uses half of the study time within the semester to solve and document a real-world engineering problem. Working with problems gives the students a very deep learning of the subjects they study, but also very good problem solving skills and team work competencies that are highly recommended by the Danish companies. In the first years of the university many students had difficulties with practical issues such as collaboration, communication, and project management. An important aspect of the basic part of the education (first year), has therefore been the development of a course where the students gets tools and tricks for good communication, collaboration, learning and project management (CLP). Although the course was a good help to a lot of students it was not everyone that was using the tools in their project work, and since it is only possible to learn about these issues by actually doing them the students had to deliver not only a written report documenting the results of their project, but also an analysis of the working process getting there. Since year 1998 the teachers giving the CLP course have focused very much on these process analyses and as they are a part of the examination the students also have focused more on how they work together and plan and do the project. This has clearly improved the students team and project work skills, which the CLP-teachers can see and document because they have read all of the process analyses every year since year 1998. This paper will explain the content and the form of the CLP-course and give some examples of the student’s exercises and outcome of the course in terms of the process analyses. Results from a new Danish survey will document that not only are the engineering students from Aalborg University highly requested by companies, but there is also a much lower drop out rate among the students and a dramatically higher rate of students finishes their study within the prescribed time, compared to other Danish universities and engineering schools.